Electrical characterisation of deep level defects in Be-doped AlGaAs grown on (100) and (311)A GaAs substrates by MBE - Mari, Riaz H (Springer, 2011)
The growth of high mobility two-dimensional hole gases (2DHGs) using GaAs-GaAlAs heterostructures has been the subject of many investigations. However, despite many efforts hole mobilities in Be-doped structures grown on (100) GaAs substrate remained considerably lower than those obtained by growing on (311)A oriented surface using silicon as p-type dopant. In this study we will report on the properties of hole traps in a set of p-type Be-doped Al(0.29)Ga0(.71)As samples grown by molecular beam epitaxy on (100) and (311)A GaAs substrates using deep level transient spectroscopy (DLTS) technique. In addition, the effect of the level of Be-doping concentration on the hole deep traps is investigated. It was observed that with increasing the Be-doping concentration from 1 × 10(16 )to 1 × 10(17 )cm(-3 )the number of detected electrically active defects decreases for samples grown on (311)A substrate, whereas, it increases for (100) orientated samples. The DLTS measurements also reveal that the activation energies of traps detected in (311)A are lower than those in (100). From these findings it is expected that mobilities of 2DHGs in Be-doped GaAs-GaAlAs devices grown on (311)A should be higher than those on (100).